Catalysis of impurities coalescence by quantized vortices in superfluid helium with nanofilaments formation - Gordon, E.B.; Okuda, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The dramatic effect of quantized vortices in superfluid helium on the rate of coalescence of suspendedimpurities has been predicted; such catalytic process should result in formation of fiber-like structures having primarily nanothickness. That should be valid for any impurity and it may be used as a base for the universal method of nanowires and nanotubes producing. The experiments on molecular hydrogen imbedding into liquid helium supported these conclusions. They showed that: (i) in normal liquid He the coalescence led to formatting spherical microparticles carried by turbulent motion of a liquid; (ii) in the superfluid only very long filaments were observed, they behaved as quantized vortices should do. Thesefilaments are fiber-like hydrogen crystals and they survived liquid helium transition to normal state. The promises for using this phenomenon in basic and applied sciences have been outlined.